2021
DOI: 10.1111/asj.13614
|View full text |Cite
|
Sign up to set email alerts
|

Cashew nut shell liquid potentially mitigates methane emission from the feces of Thai native ruminant livestock by modifying fecal microbiota

Abstract: The methane‐mitigating potency of cashew nutshell liquid (CNSL) was evaluated by investigating gas production from batch cultures using feces from Thai native ruminants that had been incubated for different periods. Feces was obtained from four Thai native cattle and four swamp buffaloes reared under practical feeding conditions at the Kasetsart University farm, Thailand. Fecal slurry from the same farm was also included in the analysis. CNSL addition successfully suppressed the methane production potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…A variety of studies have reported that the cashew nut shell liquid (CNSL), a phenolic subproduct of cashew nut production, has the potential to reduce ruminal methane emissions through the modification of the microbiome [ 156 , 157 , 158 , 159 , 160 ]. In a small cohort of Holstein cows, animals were subjected to a diet containing concentrate and hay (60:40) for four weeks (control time point) and then to the same diet supplemented with pellets containing 4 g/100 kg of body weight per day of CNLS (CNLS time point).…”
Section: Prevotella and Its Association With Reduced Methane...mentioning
confidence: 99%
“…A variety of studies have reported that the cashew nut shell liquid (CNSL), a phenolic subproduct of cashew nut production, has the potential to reduce ruminal methane emissions through the modification of the microbiome [ 156 , 157 , 158 , 159 , 160 ]. In a small cohort of Holstein cows, animals were subjected to a diet containing concentrate and hay (60:40) for four weeks (control time point) and then to the same diet supplemented with pellets containing 4 g/100 kg of body weight per day of CNLS (CNLS time point).…”
Section: Prevotella and Its Association With Reduced Methane...mentioning
confidence: 99%